Total protein concentration and total bacterial loadasmeasuresof residual interproximal plaque in comparative clinical trials - Nebojsa Milanovich, Jinling Wei, (Blackwell Synergy, 2008)
Aim: Establish total protein concentration and total bacterial load as quantitative measures of residual interproximal plaque (IPP) in a clinical model designed to evaluate oral hygiene interventions. Material and Methods: This clinical model was a randomized, examiner and laboratory technician-blinded, parallel-design study whereby levels of residual IPP were compared for subjects using a manual toothbrush or a toothbrush1floss. Differences between interventions were compared after 7 and 21 days of use. Protein concentration was measured using 3-(4-carboxybenzoyl) quinoline-2-carboxaldehyde in a fluorescence microplate format and bacterial load was assessed by quantitative real-time PCR with universal primers specific for 16S rRNA and detected by SYBR Green. ANCOVA was used to assess the statistical significance of the differences between interventions while clinical relevance was evaluated by a statistical model described by Man-Son-Hing et al. 2002. Results: Ninety-three subjects completed the study. Significant differences between interventions, using both outcome measures, were observed after 7 and 21 days. The difference between interventions by total protein concentration were further determined to be clinically relevant. Conclusions: Only total protein concentration provided both statistically significant and clinically relevant differences between two clinically distinct oral hygiene interventions in this clinical model for evaluating IPP.